What is urban violence? - Pavoni, A. (2019)
Considering the absence of an agreed definition of urban violence, this article suggests that exploring the violence-security nexus in the context of planetary urbanisation provides some necessary steps for theorisation. Moving from the analytical toward the conceptual, we offer three conceptual shifts, intended as steps toward a theory of urban violence: first, from violence in the city to violence in/of/through an age of planetary urbanisation; second, beyond the dichotomous thinking about the violence-security nexus; third, from manifestations of violence in the city to the ‘threshold’ (of visibility) beyond which a city is understood, and depicted, as violent.